Avaliação do desgaste mútuo da liga metálica amorfa vit-105 para aplicação diversas e na utilização para confecção de engrenagens - Salgado, Felipe Raphael (2019)
Metalic glasses are metastable materials produced with very high cooling rates to avoid crystal nucleation. The lack of long-range atomic order may provide better properties to amorphous alloys compared to conventional crystalline ones. Some Zirconium-based amorphous metallic alloys, called Vitreloy family, have excellent glass forming ability and properties for structural and industrial applications, such as high mechanical resistance at low temperatures, resilience and corrosion resistance. Due to their properties, some Vitreloy alloys have been used to make micro gears that have shown effective especially for aerospace industry. However, there are sparse studies that evaluate the mutual wear between pairs produced with these alloys, as occurs between the teeth of the mentioned micro gears. This study aims to evaluate the resistance to mutual wear between parts manufactured using Vitreloy-105 alloy by using a pin-ondisk tribometer. The pairs of specimens were produced by casting from a commercial bar and characterized by X-ray diffraction and differential scanning calorimetry to confirm, respectively, the amorphous structure of the parts and the expected thermal parameters. Contact surfaces were prepared according to ASTM G-99 tribological test standard. Wear tests were performed with three different values of normal load on the pin, keeping the rotation and sliding distance constant to obtain friction coefficients. Wear was quantified by mass loss and surface roughness was analyzed before and after tribological tests by using a profilometer. Images obtained by scanning electron microscopy allows the verification of the main wear mechanisms present in the samples and to correlate them with the applied loads. The results presented satisfactory values and consistent with the specialized literature for similar materials, showing that Vitreloy-105 alloy can have promising applications when one of the main mechanical stresses is wear.